Adjuvant tamoxifen adherence in male patients with breast cancer: An ongoing challenge - Falkson, Carla I. (Cancer, 2022)
Male breast cancer, a rare disease, is usually treated with adjuvant tamoxifen during early stages. Unfortunately, studies suggest a high rate of discontinuing adjuvant tamoxifen, but reasons for stopping this treatment are not always clear, and additional studies investigating this are needed.